2001
DOI: 10.1161/01.hyp.37.3.851
|View full text |Cite
|
Sign up to set email alerts
|

ACE D/I Polymorphism and Incidence of Post-PTCA Restenosis

Abstract: Abstract-Early restenosis is the major complication of percutaneous transluminal coronary angioplasty (PTCA), occurring in Ϸ30% of all initially successful procedures. The D/I polymorphism of the ACE gene, which has variably been reported to represent a risk factor for manifestations of ischemic heart disease, has recently been implicated in the pathophysiology of restenosis after PTCA by some investigators but not by others. All studies conducted thus far involved relatively small sample sizes. We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Patients who bear the DD genotype of the ACE gene and who are thus genetically prone to increased ACE activity [14] were initially suggested to have a greater risk of restenosis after percutaneous coronary angioplasty compared to patients with the ID or II genotype [21]. However, larger and more rigorous studies [22][23][24] found weaker associations between the ACE DD genotype and restenosis after percutaneous coronary angioplasty, with or without additional stenting. In accordance, a meta-analysis reported an inverse correlation between study population size and magnitude of relative risk associated with I/D polymorphism [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who bear the DD genotype of the ACE gene and who are thus genetically prone to increased ACE activity [14] were initially suggested to have a greater risk of restenosis after percutaneous coronary angioplasty compared to patients with the ID or II genotype [21]. However, larger and more rigorous studies [22][23][24] found weaker associations between the ACE DD genotype and restenosis after percutaneous coronary angioplasty, with or without additional stenting. In accordance, a meta-analysis reported an inverse correlation between study population size and magnitude of relative risk associated with I/D polymorphism [25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested before [23] that intimal hyperplasia in experimental models of vascular injury, in which smooth muscle cell proliferation is of major importance, may differ from the pathophysiological characteristics of restenosis after percutaneous coronary angioplasty in humans, in which adventitial remodeling and smooth muscle cell migration rather than proliferation appear to be the principle mechanisms. The same may hold true for AV fistula stenosis, in which adventitial remodeling and migration of smooth muscle cells and of fibroblasts to the intima came to be considered key events [31].…”
Section: Discussionmentioning
confidence: 99%
“…Following these initial observations, two larger studies performed in Germany [3] and Denmark [4] yielded negative results, casting doubts about the predictive value of the ID polymorphism in this process. The study of the ID polymorphism as a marker of risk for restenosis after balloon angioplasty resulted in similarly contradictory findings between a small positive study [5] and subsequent negative larger investigations [6]. Recently, a metaanalysis has assessed the value of the D allele as a marker for restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…As the angiotensin converting enzyme insertion or deletion (I/D) polymorphism is strongly associated with plasma and cellular angiotensin converting enzyme concentrations, it has been considered a strong candidate 2. It has been suggested that the incidence of coronary restenosis after a percutaneous coronary intervention is much higher in patients with the angiotensin converting enzyme DD genotype (which is associated with particularly high plasma angiotensin converting enzyme levels) than in others, but published observational studies are conflicting 318. To help clarify the evidence we considered all available relevant studies in a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%